Travel journal: Literacy practices and social skills development in eighth grade students of the rural institution Colegio Integrado Nuestra Señora de la Paz - Jaimes Niño, Laura Daniela; Parra Ruíz, Angie Daniela (Rastros Rostros, 2024)
The purpose of the article is to present the results of the Proyecto Pedagógico: Diario de viajes created in practice I, II, III and implemented in the institution Colegio Integrado Nuestra Señora de la Paz, located in La Putana village, Tienda Nueva town center. In this, the construction of el Diario de viajes is proposed as a bound to fortify the following social skills: assertiveness, active listening, effective communication, and empathy. The methodology applied in this work is developed on the qualitative ethnographic approach through participatory observation technique, in which various didactic sequences were constructed focused on the textual production of four types of text: letter, chronicle of The Indies, bestiary and description of local customs; accompanied by the expression of the aforementioned social skills. The results describe what was achieved with the production of each of the indicated typologies. In terms of written production, there are some elements of this process such as: presentation of the text, orthography, redaction and development of ideas. As well as competencies acquired through the development of the proposed social skills. Finally, the conclusions address the importance of working on these soft skills to improve interpersonal relationships, which enhances a positive school climate, a basic condition for the development of learning.
Keywords: education; writing; social skills; rural institution; pedagogical practice